Art with a message protest and propaganda. (White Plains, N.Y. Center for Humanities, 1971)
Shows how art has been used as a vehicle for propaganda and protest, as seen in such things as the Mussolini paintings and the symbol of the clenched fist. Describes the power of art to persuade through distortion. Tells how wars, governments, legislators, and political systems have been dealt with satirically in art. Provides examples from the paintings of Daumier, Hogarth, and Shahn and from the literary works of Dickens, Swift and Orwell.
Keywords: World politics -- Caricatures and cartoons; Humanities; Art studies